Theorizing Ocean Governance: A Framework Combining Governance, Science, and Law - Schøning, Lena, (Brill Research Perspectives in Humanities and Social Sciences., 2024)
Ocean governance is emerging as a field of study drawing on and combining different knowledge domains, including governance, science, and law. Assumptions of these three knowledge domains and their relationships are rarely discussed. This study attempts to contribute to such discussion by theory-building: investigating the governance-science and governance-law interfaces in an ocean governance context. The investigations form the basis for offering some perspectives concerning key topics of ocean governance: cross-sectoral, holistic, and integrated approaches, science-based decision-making, adaptation, the ecosystem approach, and ocean governance as an emerging field of study.